Heat-conducting filler for cable and preparation method of heat-conducting filler
By forming a three-dimensional porous structure by polydeposition and annealing of MXenes materials in alkali liquid, the problems of insufficient heat dissipation performance of ceramic powder in conductive cables and excessive filling amount of thermally conductive fillers are solved, and efficient heat dissipation effect and suitable mechanical properties are achieved.
Patent Information
- Application Number
- CN202411260065.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The heat dissipation performance of ceramic powder in existing conductive cables cannot be fully utilized, and high fill volume thermal conduction fillers will weaken the mechanical properties and stability of the product. MXenes materials have poor heat dissipation effect due to heavy stacking between nanosheets and self-supporting structures.
By polyprecipitating and alkalizing the MXenes material under the action of alkali liquid, modified nanosheets with special structures are formed, and freeze-drying and annealing are carried out to form a three-dimensional porous structure, increasing the heat dissipation area and optimizing the heat transfer path.
It significantly improves the thermal conductivity and heat dissipation effect of thermally conductive fillers. It is suitable for high-demand conductive cables, and has a specific gravity lower than that of traditional ceramic powders. It is suitable for applications with low filling amounts.
Smart Images

Figure BDA0005035282600000071 
Figure HDA0005035282610000011 
Figure HDA0005035282610000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a heat-conductive filler for a cable and a preparation method thereof. Background Art
[0002] Conductive cables are widely used in the existing new energy field. With the iteration of new energy technology, higher requirements are placed on the heat dissipation performance of conductive cables. At present, most of the thermal conductive fillers used in conductive cables are micron or nano-scale ceramic powders such as aluminum oxide, aluminum nitride, and silicon nitride. However, due to the upper limit of the filler filling amount of conductive cables, the heat dissipation performance of such ceramic powders cannot be fully utilized. If a high amount of thermal conductive fillers is introduced into conductive cables, the mechanical properties, electrical properties, and even stability of the product may be seriously weakened.
[0003] MXenes are a new type of two-dimensional nanomaterial, generally prepared by etching. This material is composed of transition metal carbides, nitrides or carbonitrides with a thickness of several atomic layers. It has the characteristics of high specific surface area, high thermal conductivity and high mechanical properties. It is currently mainly used in the field of energy storage, and in theory it is very suitable for replacing traditional ceramic powders for heat dissipation fillers for cables. However, in actual applications, MXenes will have a phenomenon of heavy stacking between nanosheets, or form a self-supporting structure, resulting in a small specific surface area or poor dispersion during application, and cannot achieve good thermal conductivity. MXenes prepared by etching have poor thermal conductivity due to their own structural and composition defects, and it is difficult to achieve the heat dissipation level of traditional ceramic powders. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a method for preparing a thermally conductive filler for a cable. First, the MXenes material is precipitated and alkalized under the action of an alkali solution to form a modified nanosheet MXenes material with a special structure. Subsequently, after freeze-drying and annealing, the functional groups in the material undergo a directional transformation, and a three-dimensional porous structure is finally formed. The final product has a large heat dissipation area and an efficient heat transfer path, and has an excellent heat dissipation effect.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a thermally conductive filler for a cable comprises the following steps:
[0007] (1) etching, cleaning, ultrasonically dispersing, and centrifuging the precursor material to obtain a MXenes material suspension;
[0008] (2) adding an alkaline solution to the MXenes suspension and stirring until flocculent precipitation occurs, standing, separating the solid, washing, and freeze-drying to obtain a modified MXenes material; the concentration of the alkaline solution is ≥5 mol / L;
[0009] (3) The modified MXenes material is annealed to obtain the thermal conductive filler for the cable.
[0010] The difference between the thermally conductive filler for cables of the present invention and the preparation method of traditional MXenes materials is that MXenes materials are prepared in advance, and then an alkaline solution is introduced for stirring and standing treatment. In this process, the cations in the alkaline solution will cause the nanosheet structure in the MXenes material to rapidly aggregate and precipitate through electrostatic action, and at the same time form a special three-dimensional porous structure, which greatly increases the heat dissipation area of the obtained product and optimizes the heat transfer path. At the same time, hydroxide ions will undergo functional group substitution on the surface of the MXenes material. After freeze-drying and annealing treatment, the hydroxide ions on the surface of the material will be converted into oxygen-containing groups, which greatly improves the phonon scattering probability of the material, and the thermal conductivity of the thermally conductive filler for cables finally prepared is significantly improved.
[0011] If the alkaline solution is not modified during the product preparation process, or the concentration of the alkaline solution is low and the degree of modification is low, the heat dissipation of the product may not be improved. On the other hand, if annealing is not performed after alkaline solution treatment, there are more hydroxide ions on the surface of the product, which cannot be converted into oxygen-containing groups with a gain effect. Instead, the thermal conductivity of the product will deteriorate. Each stage of processing is indispensable.
[0012] Preferably, the precursor material is at least one of Ti3AlC2, Ti2AlC, V4AlC3, and V2AlC.
[0013] Preferably, the etching treatment in step (1) is performed by soaking the precursor material in an etching solution, and the etching solution comprises hydrochloric acid and lithium fluoride;
[0014] More preferably, during the soaking, after the etching solution no longer generates bubbles, the solution is stirred at 40-50° C. for 45-50 hours.
[0015] More preferably, the etching solution is a mixture of hydrochloric acid and lithium fluoride, the mass concentration of the hydrochloric acid is 35-40%, and the ratio of the volume of the hydrochloric acid to the mass of the lithium fluoride is (20-30) mL: 1 g.
[0016] The MXenes material prepared by the etching method has a low degree of re-stacking and self-support in its lamellar structure, but its own heat dissipation is poor. The method described in the present invention is to further give the MXenes material obtained by the etching method a material structure and surface functional groups with high heat dissipation through alkali immersion coagulation, freeze drying and annealing processes, and the material obtained by the above-mentioned preferred etching process has a better effect of further modification.
[0017] Preferably, in step (2), the concentration of the MXenes material suspension is 5 to 8 g / L.
[0018] Preferably, the alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution.
[0019] More preferably, the concentration of the alkaline solution is 6 to 9 mol / L.
[0020] More preferably, the volume ratio of the MXenes material suspension to the alkaline solution is (0.8-1.2): (0.8-1.2).
[0021] When a low-concentration alkaline solution is used to modify the MXenes material, it not only fails to optimize the structure and surface functional groups of the MXenes material, but may even destroy the structure of the MXenes material to a certain extent due to oxidation. When a high-concentration alkaline solution within the above preferred range is selected for modification, since the dissolved oxygen content in the solution itself is low and it will passivate the MXenes material, it can optimize the structure and functional groups while ensuring that the structure will not be damaged.
[0022] Preferably, in step (2), the standing time is 8 to 12 hours.
[0023] After the flocculent precipitate is formed, the obtained material is further placed in an alkaline solution for alkalization treatment. The fluorine groups on the surface of the MXenes material are replaced by hydroxide groups. At the same time, the structure of the MXenes material will not be destroyed during the process, and a three-dimensional porous structure is gradually formed.
[0024] Preferably, the annealing treatment in step (3) is performed under an inert atmosphere.
[0025] More preferably, the temperature during the annealing treatment is 300-400° C., and the time is 8-12 hours.
[0026] The annealing process under the above-mentioned preferred conditions can more effectively convert the -F groups and -OH groups on the surface of the original MXenes material into -O groups, thereby improving the thermal conductivity of the product. At the same time, the material structure has better dispersion and the overall heat dissipation effect is better.
[0027] Another object of the present invention is to provide a thermally conductive filler for a cable prepared by the method for preparing the thermally conductive filler for a cable.
[0028] Another object of the present invention is to provide a conductive cable, comprising the thermally conductive filler for the cable of the present invention.
[0029] Preferably, the conductive cable includes a photovoltaic cable or an EV charging cable.
[0030] The thermally conductive filler for cable described in the present invention has ideal performance in heat dissipation due to its special three-dimensional porous structure and the setting of surface functional groups. After the sample containing the product is continuously heated at 180°C for 1 hour, the temperature of the sample can be maintained below 70°C, and the heat dissipation effect is excellent. At the same time, it is essentially a modified MXenes material with a specific gravity much lower than that of traditional ceramic powders. Therefore, it is very suitable for various types of conductive cables that have high requirements for heat dissipation performance but the filler filling amount cannot be too high.
[0031] The beneficial effect of the present invention is that the present invention provides a method for preparing a thermally conductive filler for a cable. First, the MXenes material is precipitated and alkalized under the action of an alkali solution to form a modified nanosheet MXenes material with a special structure. Subsequently, after freeze-drying and annealing, the functional groups in the material undergo a directional transformation, and a three-dimensional porous structure is finally formed. The final product has a large heat dissipation area and an efficient heat transfer path, and has an excellent heat dissipation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a real picture of the suspension prepared by the preparation method described in Example 1 of the present invention;
[0033] Figure 2 The real-time temperature diagram of the product obtained in Example 1 of the present invention during the heating test, wherein the left figure a is a test result diagram when the heating setting temperature is 90° C., and the right figure b is a test result diagram when the heating setting temperature is 180° C.;
[0034] Figure 3 The real-time temperature diagram of the product obtained in Comparative Example 1 of the present invention during the heating test, wherein the left figure a is a test result diagram when the heating setting temperature is 90°C, and the right figure b is a test result diagram when the heating setting temperature is 180°C;
[0035] Figure 4 The real-time temperature diagram of the product obtained in Comparative Example 2 of the present invention during the heating test, wherein the left figure a is a test result diagram when the heating setting temperature is 90° C., and the right figure b is a test result diagram when the heating setting temperature is 180° C.;
[0036] Figure 5The real-time temperature diagram of the product obtained in Comparative Example 3 of the present invention during the heating test, wherein the left figure a is a test result diagram when the heating setting temperature is 90°C, and the right figure b is a test result diagram when the heating setting temperature is 180°C;
[0037] Figure 6 The real-time temperature diagram of the product obtained in Comparative Example 4 of the present invention during the heating test, wherein the left figure a is a test result diagram when the heating setting temperature is 90° C., and the right figure b is a test result diagram when the heating setting temperature is 180° C.;
[0038] Figure 7 This is a physical picture of the product obtained in Example 1 of the present invention;
[0039] Figure 8 The figures are the physical pictures of the products obtained in the comparative examples of the present invention, wherein the upper left figure a is the physical picture of the product obtained in comparative example 1, the upper right figure b is the physical picture of the product obtained in comparative example 2, the lower left figure c is the physical picture of the product obtained in comparative example 3, and the lower right figure d is the physical picture of the product obtained in comparative example 4;
[0040] Fig. 9 This is a scanning electron microscope image of the product obtained in Example 1 of the present invention;
[0041] Fig.10 These are scanning electron microscope images of the products obtained in each comparative example of the present invention, wherein the upper left figure a is a scanning electron microscope image of the product obtained in comparative example 1, the upper right figure b is a scanning electron microscope image of the product obtained in comparative example 2, the lower left figure c is a scanning electron microscope image of the product obtained in comparative example 3, and the lower right figure d is a scanning electron microscope image of the product obtained in comparative example 4. DETAILED DESCRIPTION
[0042] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0043] Example 1
[0044] An embodiment of a thermally conductive filler for a cable and a preparation method thereof according to the present invention, wherein the preparation method of the thermally conductive filler for a cable comprises the following steps:
[0045] (1) 2 g of the precursor material Ti3AlC2 was placed in an etching solution obtained by mixing 50 mL of 36% mass concentration hydrochloric acid and 2 g of lithium fluoride for etching until no bubbles were generated in the obtained mixture, and then stirred at 150 rpm at 45 ° C for 48 h, the solid was filtered, and then washed with deionized water, and ultrasonically dispersed with 200 mL of deionized water for 1 h, and then centrifuged at 2000 rpm to obtain a MXenes material suspension, and the suspension was irradiated with light, such as Figure 1 As shown, it can be seen that the suspension has Tyndall effect and the material has good suspension properties;
[0046] (2) Take 50 mL of the MXenes material suspension separately, add 50 mL of 6 mol / L potassium hydroxide solution thereto and stir until flocculent precipitation appears, let stand for 10 h for alkalization treatment, separate the solid, wash with deionized water, and freeze-dry at -55 ° C and -0.06 MPa for 24 h to obtain a modified MXenes material;
[0047] (3) The modified MXenes material is annealed at 400° C. for 12 h in an argon atmosphere to obtain the thermal conductive filler for the cable.
[0048] Example 2
[0049] The embodiment of a thermally conductive filler for a cable and a preparation method thereof described in the present invention is different from Example 1 only in that the precursor material Ti3AlC2 is replaced by Ti2AlC.
[0050] Example 3
[0051] The embodiment of a thermally conductive filler for a cable and a preparation method thereof described in the present invention is different from Example 1 only in that the precursor material Ti3AlC2 is replaced by V2AlC.
[0052] Example 4
[0053] The embodiment of a thermally conductive filler for a cable and a preparation method thereof according to the present invention is different from Embodiment 1 only in that the concentration of the potassium hydroxide solution is 7.5 mol / L.
[0054] Example 5
[0055] The embodiment of a thermally conductive filler for a cable and a preparation method thereof according to the present invention is different from Embodiment 1 only in that the concentration of the potassium hydroxide solution is 9 mol / L.
[0056] Comparative Example 1
[0057] A thermally conductive filler for a cable and a preparation method thereof, which differs from Example 1 only in that the preparation method of the thermally conductive filler for a cable comprises the following steps:
[0058] 2 g of the precursor material Ti3AlC2 was placed in an etching solution obtained by mixing 50 mL of 36% mass concentration hydrochloric acid and 2 g of lithium fluoride for etching until no bubbles were generated in the obtained mixed solution. The mixture was then stirred at 150 rpm at 45°C for 48 hours. The solid was filtered and washed with deionized water. 200 mL of deionized water was ultrasonically dispersed for 1 hour. The mixture was then collected by centrifugation at 2000 rpm to obtain a MXenes material suspension. The suspension was freeze-dried at -55°C and -0.06 MPa for 24 hours to obtain the thermal conductive filler for the cable.
[0059] Comparative Example 2
[0060] A thermally conductive filler for a cable and a preparation method thereof, which differs from Example 1 only in that the preparation method of the thermally conductive filler for a cable comprises the following steps:
[0061] (1) 2 g of the precursor material Ti3AlC2 was placed in an etching solution obtained by mixing 50 mL of 36% mass concentration hydrochloric acid and 2 g of lithium fluoride for etching until no bubbles were generated in the obtained mixed solution, and then stirred at 150 rpm at 45 ° C for 48 h, the solid was filtered, and then washed with deionized water, and ultrasonically dispersed with 200 mL of deionized water for 1 h, and then centrifuged at 2000 rpm to obtain a MXenes material suspension, which was freeze-dried at -55 ° C and -0.06 MPa for 24 h to obtain a modified MXenes material;
[0062] (2) The modified MXenes material is annealed at 400° C. for 12 h in an argon atmosphere to obtain the thermal conductive filler for the cable.
[0063] Comparative Example 3
[0064] A thermally conductive filler for a cable and a preparation method thereof, which differs from Example 1 only in that the preparation method of the thermally conductive filler for a cable comprises the following steps:
[0065] 2 g of the precursor material Ti3AlC2 was placed in an etching solution obtained by mixing 50 mL of 36% mass concentration hydrochloric acid and 2 g of lithium fluoride for etching until no bubbles were generated in the obtained mixed solution, and then stirred at 45°C for 48 hours at a rotation speed of 150 rpm, the solid was filtered, and then washed with deionized water, ultrasonically dispersed with 200 mL of deionized water for 1 hour, and then centrifuged and collected at a speed of 2000 rpm to obtain a MXenes material suspension, and then 50 mL of the MXenes material suspension was taken separately, 50 mL of a 6 mol / L potassium hydroxide solution was added thereto and stirred until a flocculent precipitate appeared, and the mixture was allowed to stand for 10 hours for alkalization treatment, the solid was separated, washed with deionized water, and freeze-dried for 24 hours under the conditions of -55°C and -0.06 MPa to obtain the thermal conductive filler for the cable.
[0066] Comparative Example 4
[0067] A thermally conductive filler for a cable and a preparation method thereof, the difference from Example 1 being that the concentration of the potassium hydroxide solution is 3 mol / L.
[0068] Effect Example 1
[0069] In order to verify the use effect of the thermal conductive filler for cable of the present invention, the thermal conductive filler for cable of each embodiment and comparative example was processed into a test sample. The processing method was as follows: 30 mg of the thermal conductive filler was taken, cold pressed into a sheet by a tablet press, and trimmed into 3×3 cm 2 The square specimens were tested with a tabletting load of 5 MPa and a loading time of 5 min.
[0070] The samples were then heated in an oven at 90°C and 180°C for 1 hour. The real-time temperature of the samples was recorded every 5 minutes. Finally, the maximum value of the real-time temperature of the samples in each period was recorded for statistics. The results are shown in Table 1.
[0071] Table 1
[0072]
[0073]
[0074] It can be seen from the results that the thermally conductive filler for cable of the present invention has ideal thermal conductivity. After heating at 90°C for 1 hour, the test sample can basically maintain at about 40°C, and after heating at 180°C for 1 hour, it can basically maintain at about 60°C.
[0075] In contrast, the thermal conductivity of the comparative examples is not ideal, and their maximum real-time temperatures are significantly lower than those of the examples whether heated at 90°C or 180°C.
[0076] The statistical data of the test samples of Example 1 and Comparative Examples 1 to 4 are summarized, and the results are as follows: Figures 2 to 6 As shown, it can be seen that when the heating program is set at 90°C, since the heating temperature is close to the real-time temperature of the sample, the thermal conductive filler has an obvious heat dissipation effect, so the real-time temperature of the environment fluctuates to a certain extent in different time periods, but the real-time temperature of the sample is basically stable, indicating that the thermal conductive filler in each sample starts to dissipate heat at the initial stage of heating and the heat dissipation rate is relatively stable. At 180°C, both the ambient temperature and the real-time temperature of the sample are relatively stable, and the real-time temperature of the samples processed with the comparative thermal conductive filler is much higher than that of the samples obtained in Example 1.
[0077] The products obtained in Example 1 and Comparative Examples 1 to 4 were observed. Figure 7 and 8 As shown, it can be seen that the thermal conductive filler for cable obtained in Example 1 has high looseness and is in a highly dispersed powder state, while the MXenes material in the product of Comparative Example 1 that has not been treated with alkaline solution for modification and annealing treatment shows obvious agglomeration during freeze-drying, and the product is in block form. Even subsequent crushing and grinding cannot optimize the microscopic agglomerated self-supporting structure, so the thermal conductivity of the product is low; the product of Comparative Example 2 is annealed on the basis of Comparative Example 1, but the morphology is not significantly different from that of the product of Comparative Example 1, indicating that alkaline solution treatment is the key to product structure optimization; the product of Comparative Example 3 is treated with alkaline solution, so it has good dispersibility; although the product of Comparative Example 4 is modified with alkaline solution and annealed, it is still in block form. The main reason is that the low concentration of alkaline solution not only cannot optimize the structure of the MXenes material, but also converts Ti in part of the material into TiO2 due to oxidation reaction, thereby destroying the material structure, a self-supporting structure appears in the product, and white TiO2 particles exist on the surface.
[0078] Furthermore, the products obtained in Example 1 and Comparative Examples 1 to 4 were observed using a scanning electron microscope. The results are as follows: Fig. 9 and 10As shown, it can be seen that at the microscopic scale, the product obtained in Example 1 has an ideal three-dimensional porous structure, which is attributed to the treatment step of coagulation modification of MXenes materials in alkaline solution, while the product obtained in Comparative Example 1 also has a three-dimensional porous structure, but the three-dimensionality is slightly weaker. The main reason is that the product described in Comparative Document 1 was freeze-dried during preparation, and water molecules will form ice crystal templates during this process, thereby giving the product a certain three-dimensional porous structure; similarly, the product of Comparative Example 2 was also freeze-dried, so its morphology is similar to that of Comparative Example 1; the product of Comparative Example 3 was not annealed compared to the product of Example 1, and was similar to the product of Example 1 from the microscopic morphology, indicating that the annealing treatment is mainly to regulate the surface functional groups of the product, while the regulation range of the morphology structure is small; although the product of Comparative Example 4 also presents a certain three-dimensional porous structure, the three-dimensional sense is low, the spacing between the nanosheet layers is small, and a small amount of white particles appear on the surface of the nanosheet layer, corresponding to the actual picture.
[0079] In order to further study the effects of alkaline solution treatment and annealing treatment on the chemical composition of the product in the product preparation method of the present invention, the products of Example 1 and Comparative Examples 1 to 4 were subjected to elemental content analysis and XPS analysis (peak fitting to confirm the functional group distribution, where the larger the relative area, the greater the proportion of functional group distribution on the product surface), and the results are shown in Tables 2 and 3.
[0080] Table 2
[0081] Element content (at%) Ti C O F K Example 1 35.8 24.6 33.7 2.6 2.9 Comparative Example 1 39.3 26.5 19.6 13.9 / Comparative Example 2 39.1 27.6 20.1 12.8 / Comparative Example 3 34.6 25.6 29.4 7.7 2.5 Comparative Example 4 24.5 33.6 36.8 2.8 2.2
[0082] Table 3
[0083] Relative area (%) Ti-O Ti-F Ti-OH Example 1 80.6 7.8 11.6 Comparative Example 1 47.8 35.5 16.7 Comparative Example 2 55.3 33.6 11.1 Comparative Example 3 53.5 25.2 21.3 Comparative Example 4 81.7 8.2 10.1
[0084] As can be seen from Table 2, the product of Comparative Example 1 has not been subjected to alkaline solubility treatment modification and annealing treatment, while the product of Example 1 has been subjected to the above treatment. The relative contents of Ti and C elements of the two products are similar, but the relative amount of O element of the product of Example 1 is significantly increased, and the relative content of F element is significantly reduced, indicating that after the above treatment, the fluorine-containing group is replaced by the oxygen-containing group, and the further converted oxygen-containing group has a significant gain in the heat dissipation performance of the product. The product of Comparative Example 2 has not been subjected to alkaline solution treatment, but only to annealing treatment. The content of each element is close to that of the product of Comparative Example 1, and the F element is still detected, indicating that only after the alkaline solution treatment is first performed, The functional groups in the product can be effectively regulated; the product of Comparative Example 3 was not annealed after the alkaline solution treatment. Although the relative contents of the O and F elements showed a certain trend of change, they were far less than those of the product of Example 1; the chemical composition of the product of Comparative Example 4 was quite different from that of the other products. The relative contents of the Ti and C elements were quite different from those of the product of Comparative Example 1, and the relative content of the F element was also reduced, indicating that the MXenes material underwent an obvious oxidation reaction during the low-concentration alkaline solubility treatment. The Ti element was oxidized into white TiO2 particles, and the nanosheet structure of the material was damaged, which corresponds to the above test results.
[0085] In Table 3, the product of Example 1 has less Ti-F bonds and Ti-OH bonds than the product of Comparative Example 1, and more Ti-O bonds, mainly because the -F group is replaced by -OH during the alkaline solution treatment, and then -OH is converted to -O during the annealing treatment. This functional group can inhibit the vibration of Ti and C atoms, thereby inhibiting phonon scattering and improving the thermal conductivity of the product; the relative content of Ti-F bonds in the product of Comparative Example 2 has no significant change compared with the product of Comparative Example 1, while the Ti-OH bonds and Ti-O bonds have certain changes, indicating that the annealing treatment will only convert a part of the Ti-OH bonds into Ti-O bonds; the relative content of Ti-F bonds in the product of Comparative Example 3 is low, but the content of Ti-O bonds is still low, only the content of Ti-OH bonds increases, which has no obvious help in improving the thermal conductivity of the product. The functional group bond distribution of the product of Comparative Example 4 is similar to that of Example 1, indicating that a low concentration of alkaline solution will also convert the Ti-F bond, but during the conversion process, the Ti element is oxidized into white TiO2 particles. Although it also contains Ti-O bonds, the material structure is damaged, so the thermal conductivity efficiency is poor.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the present invention.
Claims
1. A method for preparing a thermally conductive filler for a cable, characterized in that: The following steps are involved: (1) etching, cleaning, ultrasonically dispersing, and centrifuging the precursor material to obtain a MXenes material suspension; (2) adding an alkaline solution to the MXenes suspension and stirring until flocculent precipitation occurs, standing, separating the solid, washing, and freeze-drying to obtain a modified MXenes material; The concentration of the alkaline solution is ≥5 mol / L; (3) The modified MXenes material is annealed to obtain the thermal conductive filler for the cable.
2. The method for preparing the thermally conductive filler for cable according to claim 1, characterized in that: The precursor material is at least one of Ti3AlC2, Ti2AlC, V4AlC3, and V2AlC.
3. The method for preparing the thermally conductive filler for cable according to claim 1, characterized in that: In the step (1), the etching treatment is performed by immersing the precursor material in an etching solution, and the etching solution includes hydrochloric acid and lithium fluoride; preferably, the etching solution is a mixture of hydrochloric acid and lithium fluoride, the mass concentration of the hydrochloric acid is 35-40%, and the ratio of the volume of the hydrochloric acid to the mass of the lithium fluoride is (20-30) mL: 1 g.
4. The method for preparing the thermally conductive filler for cable according to claim 1, characterized in that: In (1), the concentration of the MXenes material suspension is 5 to 8 g / L.
5. The method for preparing the thermally conductive filler for cable according to claim 1, characterized in that: The alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution; preferably, the concentration of the alkaline solution is 6 to 9 mol / L.
6. The method for preparing the thermally conductive filler for cable according to claim 1, characterized in that: The volume ratio of the MXenes material suspension to the alkaline solution is (0.8-1.2): (0.8-1.2).
7. The method for preparing the thermally conductive filler for cable according to claim 1, characterized in that: In the step (2), the standing time is 8 to 12 hours.
8. The method for preparing the thermally conductive filler for cable according to claim 1, characterized in that: The annealing treatment in step (3) is carried out under an inert atmosphere; preferably, the temperature of the annealing treatment is 300-400° C. and the time is 8-12 hours.
9. The thermally conductive filler for cables prepared by the method for preparing the thermally conductive filler for cables according to any one of claims 1 to 8.
10. A conductive cable, characterized in that: It comprises the thermally conductive filler for cables as described in any one of claims 1 to 8; preferably, the conductive cable comprises a photovoltaic cable or an EV charging cable.
Citation Information
Patent Citations
Composite material with heat conduction and electromagnetic protection functions as well as preparation method and application of composite material
CN114905803A
Preparation method of alkali-induced three-dimensional porous MXene-bacterial cellulose flexible membrane electrode
CN115831480A
Transition metal carbonitride preparation method, electronic component preparation method and resistive random access memory
CN116062757A
Lignin surface modified heat-conducting filler as well as preparation method and application thereof
CN116554713A
Method for preparing boron nitride-MXene filler, coating using boron nitride-MXene filler and coating preparation method
CN117363084A